Evaluation of the Acute and Sub-Acute Oral Toxicity of Jaranol in Kunming Mice - Liu, Tianlong; Zhang, Yao; Liu, Jing; Peng, Junwen; Jia, Xin; Xiao, Yunfeng; Zheng, Lanbing; Dong, Yu (Frontiers in Pharmacology, 2022)
Background: Jaranol has shown a wide range of pharmacological activities; however, no study has yet examined in vivo toxicity. The study aimed to investigate the oral acute and sub-acute toxicity of jaranol in mice. Methods: The acute toxicity was determined by a single oral dose of jaranol (2000 mg/kg). Therein animal behaviour and mortality rate were observed for 14 days. The jaranol (50, 100 and 200 mg/kg BW·d−1) was given by gavage for 28 days daily in the sub-acute study. The mouse body weight (BW), organ weight, food, water intake, biochemical, haematological parameters, and histopathology were studied in acute and sub-acute toxicity. Results: During the acute toxicity test, a single oral dose (2000 mg/kg) jaranol did not cause significant alteration in majority of the hematological indices. However, jaranol decreased the level of serum alanine aminotransferase and aspartate aminotransferase. Those results showed that the oral lethal dose 50 (LD50) of jaranol was higher than 2000 mg/kg BW, regardless of sex. In repeated daily oral doses (50, 100 and 200 mg/kg BW·d−1), no mortality was recorded in the various experimental groups. The jaranol reduced body weight gain (200 mg/kg BW·d−1), the relative spleen weight (all doses) and serum alanine aminotransferase activity (200 mg/kg BW·d−1). On the other hand, jaranol significantly elevated red blood cell count (100 and 200 mg/kg BW·d−1) and serum creatinine levels (200 mg/kg BW·d−1). Histological study revealed that spleen bleeding was identified in 200 mg/kg jaranol-treated mice. Conclusion: Jaranol was relatively safe in Kunming Mice when repetitively administered orally in small doses for a prolonged period of time. We recommend more chronic toxicity studies and clinical trials on jaranol to ensure that its use is free of potential toxicity to humans.